Human rights in tourism : effectiveness of the legal framework for tourism in Mosambique upon the realization of the right to development of local communities - Georgijevic, Shivani (University of Pretoria, 2011)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2010.